2013
DOI: 10.1109/tro.2013.2240176
|View full text |Cite
|
Sign up to set email alerts
|

C-FOREST: Parallel Shortest Path Planning With Superlinear Speedup

Abstract: In (Otte and Correll 2013) we present C-FOREST, a parallelization framework for single-query samplingbased shortest-path planning algorithms. C-FOREST has been observed to have super linear speedup on many problems, e.g., paths of quality Ltarget are found 350X faster by 64 CPUs working in parallel than by 1 CPU. In (Otte and Correll 2013) C-FOREST is tested in conjunction with the RRT* algorithm. In the current work we perform additional experiments that show C-FOREST provides similar advantages when used con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(45 citation statements)
references
References 19 publications
1
44
0
Order By: Relevance
“…Also, the use of parallelized planning algorithms such as C-Forest [40] seems convenient in order to take advantage of modern multi-core processors. To conclude, path pruning techniques such as the proposed in [41] can be used in a post-processing step to the paths obtained with RRT* method in order to get rid of unnecessary waypoints.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the use of parallelized planning algorithms such as C-Forest [40] seems convenient in order to take advantage of modern multi-core processors. To conclude, path pruning techniques such as the proposed in [41] can be used in a post-processing step to the paths obtained with RRT* method in order to get rid of unnecessary waypoints.…”
Section: Discussionmentioning
confidence: 99%
“…Otte and Correll [39] use a parallel hybrid method in their Coupled Forest of Random Engrafting Search Trees (C-FOREST) algorithm. Demonstrated with RRT*, the algorithm shares information between multiple sampling-based planners using heuristics and rejection sampling.…”
Section: Hybridizationmentioning
confidence: 99%
“…One source of speedup has been parallelism, including the use of multiple cores or processors (e.g., [5], [7], [10], [15], [28], [35]) and GPUs (e.g., [3], [29]) to achieve speedups for single-query sampling-based motion planners (e.g., RRT and RRT*). Wedge and Branicky showed that periodically restarting sampling-based tree construction can improve the mean and the variability of the runtime of RRT [47].…”
Section: Related Workmentioning
confidence: 99%